2018
DOI: 10.3168/jds.2017-12919
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of conformation and milk yield in mixed-breed dairy goats

Abstract: Identification of genetic markers that affect economically important traits is of high value from a biological point of view, enabling the targeting of candidate genes and providing practical benefits for the industry such as wide-scale genomic selection. This study is one of the first to investigate the genetic background of economically important traits in dairy goats using the caprine 50K single nucleotide polymorphism (SNP) chip. The aim of the project was to perform a genome-wide association study for mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 65 publications
(83 reference statements)
6
58
3
1
Order By: Relevance
“…Polymorphisms affecting these genes should be assessed as potential genetic markers in relation to increased SCS in dairy sheep. Comparing with results reported in goats, we did not find a relevant coincidence, as the sheep genomic regions on OAR11 orthologous to the intervals harboring recently reported QTL on goat chromosome 19 for SCS and udder traits (Martin et al, 2018;Mucha et al, 2018;26-28 Mb and 40-42 Mb) are not coincident with the significant LDLA association reported here on OAR11 (56.8-56.9 Mb). The scarce number of goat studies on this topic may explain the lack of coincidences.…”
Section: Discussioncontrasting
confidence: 59%
“…Polymorphisms affecting these genes should be assessed as potential genetic markers in relation to increased SCS in dairy sheep. Comparing with results reported in goats, we did not find a relevant coincidence, as the sheep genomic regions on OAR11 orthologous to the intervals harboring recently reported QTL on goat chromosome 19 for SCS and udder traits (Martin et al, 2018;Mucha et al, 2018;26-28 Mb and 40-42 Mb) are not coincident with the significant LDLA association reported here on OAR11 (56.8-56.9 Mb). The scarce number of goat studies on this topic may explain the lack of coincidences.…”
Section: Discussioncontrasting
confidence: 59%
“…Such work enabled the identification of 109 significant associations and further uncovered two polymorphisms in the DGAT1 gene that have major effects on fat content by modifying the activity of this enzyme [1]. In another recent study, Mucha et al [2] detected a single nucleotide polymorphism (SNP) on goat chromosome 19 displaying a genome-wide significant association with milk yield as well as a number of chromosome-wide significant associations with dairy traits on chromosomes 4, 8, 14, and 29. Although these two studies represent a valuable step towards elucidating the genomic architecture of milk yield and composition traits in goats, analyzing a broader array of goat populations, as has been done in cattle [3], would provide a more comprehensive view of the genetic determinism of caprine dairy phenotypes.…”
Section: Introductionmentioning
confidence: 98%
“…In another study, GWAS analyses were performed in dairy goats (French Alpine and Saanen, or mixedbreed goats) to identify QTL that affect traits under selection. Martin et al (2018) and Mucha et al (2018) investigated the genetic architecture of different traits. These authors observed a large QTL associated with milk yield, fat yield, protein yield, udder floor position, rear udder attachment, and SCS on chromosome 19.…”
mentioning
confidence: 99%